De Abgail Antônio P. da Silva a Zico Barbosa: língua, história e memória nos nomes de logradouros no município de Pedro Leopoldo – MG - Letícia Rodrigues Guimarães Mendes (2022)
This thesis aimed to carry out a linguistic research focusing on the toponymic lexicon of public places in the city of Pedro Leopoldo - MG, more specifically those called by antropotopônimos, covering streets, avenues, squares, alleys, highways and roads. A municipality currently belonging to the Metropolitan Region of Belo Horizonte, Pedro Leopoldo has its past related to the presence of prehistoric man in the region, as well as, more modernly, to the São Paulo flags that pioneered the territory in search of gold and precious stones. It is proposed, with this research, to demonstrate that the study of place names is capable of providing the rescue of local memory and culture, as, through toponymy, the historical marks of societies are maintained, generation after generation. The theoretical framework of this research was based on the concepts postulated by Dauzat (1926); Sapir (1963); Dick (1990a; 1990b), Duranti (2000), Seabra (2006); Labov (2008); Faria (2017); Amaral e Seide (2020). Following the sociolinguistic models, the names of the places in the researched city were raised, within the objectives of this research. Subsequently, investigations were carried out in various laws and documents, as well as searches for family members of the honorees, in an attempt to rescue the biographies and promote the maintenance of the memory of these honorees with the names of public places in the municipality of Pedro Leopoldo. Through the analysis of the Naming Laws, it was possible to establish whether there was a variation or change in the names. Through applications Google Maps and through a paper map, the places surveyed were identified; photos of the signs of these public places were recorded, when present. For each antropotopônimo, a toponymic form was created, in which the collected data are organized. The results obtained through this research demonstrate that in the researched city there is a predominance of public places named after people from the same place, belonging to different socialstrata. There was still little variation in the names and this, when it occurred, occurred in the sense of exchanging more generic names or dates (such as Rua Várzea Formosa or Praça 31 de Março) for the names of the city's former residents. Thus, it was noted that, through the nomination, there is a great focus on the preservation of local memory in the municipality of Pedro Leopoldo.